Step-by-step explanation:
We first prove the base case, which is proving that the inequality holds for n=2:
![2^2+3^2=4+9=13<25=5^2](https://img.qammunity.org/2020/formulas/computers-and-technology/college/jzwzoy1ishmuj8444af3nopju0krlllid6.png)
So
and base case is proven.
We then do the inductive step, which is assuming that the inequality holds for n=k, and proving out of that that the inequality also holds for n=k+1:
Assume the inequality holds for n=k. This means that
![2^k+3^k<5^k](https://img.qammunity.org/2020/formulas/computers-and-technology/college/4p3iyhc273m505rljhuj2r4z2yurjn3ykd.png)
Our goal is then to show that
.
We have that
![2^(k+1)+3^(k+1)=2\cdot 2^k+3\cdot 3^k<3\cdot 2^k+3\cdot 3^k =3\cdot (2^k+3^k)<3\cdot 5^k < 5\cdot 5^k = 5^(k+1)](https://img.qammunity.org/2020/formulas/computers-and-technology/college/3tbx88xxe0phivk09qhm82uapd5kxruqn8.png)
(since we're assuming that
, we know that
).
So
, and the inductive step is proven.
Therefore we can conclude by the principle of mathematical induction that for all
![n \geq 2,~2^n+3^n<5^n](https://img.qammunity.org/2020/formulas/computers-and-technology/college/qxpjo5ox197zvqxog5azoy54z34kbje6j9.png)